2019
DOI: 10.5847/wjem.j.1920-8642.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic improvement using methylene blue after calcium channel blocker overdose

Abstract: Calcium channel blocker overdoses are often fatal despite standard treatment. Methylene blue is a novel adjunct that should be considered in refractory cases. Currently accepted therapeutic modalities include intravenous fl uids, calcium, vasopressors and high-dose insulin euglycemic therapy, however shock may persist despite these treatment options. [1] Methylene blue has been utilized in sepsis, shock after cardiac surgery and other non-poisoning causes of shock. However, there are only ten human case report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…However, it increased median survival time, mean arterial pressure and heart rate [55]. It was reported that methylene blue improves haemodynamic parameters in patients suffering from drug-induced refractory vasodilatory shock [56][57][58]. Administration of therapeutic doses, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, it increased median survival time, mean arterial pressure and heart rate [55]. It was reported that methylene blue improves haemodynamic parameters in patients suffering from drug-induced refractory vasodilatory shock [56][57][58]. Administration of therapeutic doses, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…MB does not affect the calcium channels or bypass it to increase intracellular cyclic adenosine mono phosphate (cAMP), rather, represents a clinical approach directed towards one of the underlying pathobiologies of vasoplegia in CCB overdose. Successful therapy with rapid improvement of hemodynamic status has been reported in a few cases [ 7 ]. CCBs upregulate endothelial nitric oxide synthase activity (eNOS) and increase the production of nitric oxide (NO) [ [8] , [9] ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, currently, there are no randomized control trials to support its use in CCB overdose, and evidence is currently limited to observational studies in the form of single case reports. In 2019, Ahmed and Barnes reported similar benefits of methylene blue administration in the case of amlodipine overdose [14]. Pasin et al conducted a meta-analysis of randomized trials evaluating the efficacy of methylene blue on raising mean arterial pressure in distributive shock in ICU patients with sepsis, patients' post-cardiac and liver transplant surgery [15].…”
Section: Discussionmentioning
confidence: 99%